The optimization of going management on UK racecourses using controlled water applications - Mumford, Colin (Cranfield University, 2006)
Non-uniform surface rating (going) on a racecourse increases the potential for risk of injury to competing horses and their riders. Variability in soil type and strength are the primary cause of inconsistent going. This research aimed to produce guidelines for Racecourse Managers to help them achieve uniform going by influencing the strength of the different soil types encountered on a racecourse using controlled water applications. Two models were developed, a soil-water balance to predict the mean going for a given soil type (MEGPREM), and a determination of effective irrigation model (DEFFIM) that establishes how much water is required to change a hard level of going to a preferred softer level. MEGPREM was found to provide poor predictions of going. DEFFIM was shown to be a valid model, and potentially provides Racecourse Managers with a useful tool to aid their decision making with regards to watering. A further study to determine whether different irrigation regimes affected the structure of two different soil types concluded that a regime that allows the soil to dry to a predetermined soil-water deficit and then re-wet to field capacity produced better soil physical properties than soils maintained at field capacity. Utilizing a simulated irrigation regime, directed by DEFFIM, that achieved wet/dry cycles as described, a cost analysis was carried out to compare the simulated irrigation with the actual irrigation practices at a racecourse for the 2004 and 2005 flat racing seasons. The results suggested that potentially significant savings in water consumption could be achieved with the use of DEFFIM, satisfying the requirements of the Water Act 2003, whilst still maintaining a preferred level of going. The findings of this research suggest that going management on a racecourse could be optimized with controlled water applications, potentially reducing the risk of injury to competing horses and jockeys.